Academic Adaptation Among International Students from East Asian Countries: A Consensual Qualitative Research - Li, Jiaqi; Wang, Yanlin; Liu, Xun; Xu, Yusu; Cui, TingTing (Journal of International Students, 2018)
This study used a consensual qualitative research method to explore academic adaptation experiences of international students (N = 13) from East Asia countries at a U.S. university. The analysis yielded five domains from the data (challenges, feelings, strategies, suggestions, and self-reflections). Implications for college counselors, university administrators, and future research are discussed.